Salt-fog corrosion behavior of C/SiC and its effect on ablation resistance. Issue 12 (December 2019) - Cheng, Su; Zhao, Xing; Yang, Guang; Wang, Yiguang
Abstract: Carbon fiber-reinforced silicon carbide (C/SiC) composites are significantly important candidates for thermal protection materials. The corrosion mechanism of C/SiC composite materials is the basis of their optimization and application. In this study, structural evolution of C/SiC composites fabricated by chemical vapor infiltration was investigated in the salt-fog storage environment. Furthermore, the effect of salt-fog on their ablation behaviors under oxyacetylene flame environment was studied. The ablation morphologies and corrosion mechanisms of C/SiC composites were analyzed and discussed. The results indicated that silica layer with size of c.a. 20 nm was formed on the surface of composite. The extent of corrosion in salt fog was limited, and it had little effect on the ablation behavior of the C/SiC composites, as well on the tensile strength and bending strength.